North Korea’s Troubled Economy: The Real Challenges - Hinata-Yamaguchi, Ryo (2016)
For the first time since 1980, North Korea recently held the Seventh Workers’ Party Congress, further bolstering Kim Jong-un’s rule, and claiming its status as a “responsible nuclear power”. Yet another important take-away from the congress was the Five-Year Economic Development Strategy aiming to remedy and develop the troubled economy.